Clinical trials and late‐stage drug development for Alzheimer's disease: an appraisal from 1984 to 2014. (March 2014) - Schneider, L. S.; Mangialasche, F.; Andreasen, N.; Feldman, H.; Giacobini, E.; Jones, R.; Mantua, V.; Mecocci, P.; Pani, L.; Winblad, B.; Kivipelto, M.
Abstract The modern era of drug development for Alzheimer's disease began with the proposal of the cholinergic hypothesis of memory impairment and the 1984 research criteria for Alzheimer's disease. Since then, despite the evaluation of numerous potential treatments in clinical trials, only four cholinesterase inhibitors and memantine have shown sufficient safety and efficacy to allow marketing approval at an international level. Although this is probably because the other drugs tested were ineffective, inadequate clinical development methods have also been blamed for the failures. Here, we review the development of treatments for Alzheimer's disease during the past 30 years, considering the drugs, potential targets, late‐stage clinical trials, development methods, emerging use of biomarkers and evolution of regulatory considerations in order to summarize advances and anticipate future developments. We have considered late‐stage Alzheimer's disease drug development from 1984 to 2013, including individual clinical trials, systematic and qualitative reviews, meta‐analyses, methods, commentaries, position papers and guidelines. We then review the evolution of drugs in late clinical development, methods, biomarkers and regulatory issues. Although a range of small molecules and biological products against many targets have been investigated in clinical trials, the predominant drug targets have been the cholinergic system and the amyloid cascade. Trial methods have evolved incrementally: inclusion criteria have largely remained focused on mild‐to‐moderate Alzheimer's disease criteria, recently extending to early or prodromal Alzheimer disease or 'mild cognitive impairment due to Alzheimer's disease', for drugs considered to be disease modifying. The duration of trials has remained at 6–12 months for drugs intended to improve symptoms; 18‐ to 24‐month trials have been established for drugs expected to attenuate clinical course. Cognitive performance, activities of daily living, global change and severity ratings have persisted as the primary clinically relevant outcomes. Regulatory guidance and oversight have evolved to allow for enrichment of early‐stage Alzheimer's disease trial samples using biomarkers and phase‐specific outcomes. In conclusion, validated drug targets for Alzheimer's disease remain to be developed. Only drugs that affect an aspect of cholinergic function have shown consistent, but modest, clinical effects in late‐phase trials. There is opportunity for substantial improvements in drug discovery and clinical development methods.